Legal and political intervention on language issues in Bangladesh: A sociolinguistic perspective - Awal, Abdul (INDONESIAN JOURNAL OF SUSTAINABILITY, 2023)
The article outlined the legal and political intervention on language issues in Bangladesh from a historical sociolinguistic perspective. More specifically, it chronologically criticised the constitution and laws issued regarding language for the time being by state holders. In his article, the author tried to present the current issue and the question of language policy and planning in Bangladesh. Furthermore, it showed the drawbacks of previous language acts in Bangladesh. Consequently, the article illustrates the contextual interplay between language policy and linguistic rights in Bangladesh. This article used data from primary sources (constitution and government orders, ordinances, and circulations, etc.) to draw some preliminary conclusions about the challenges involved in the language controversy. One of its central themes was the linguistic rights of ethnic people, minor communities, and indigenous language speakers respectively. This article investigated how state politics and language historically affected each other. The analytical framework of the article is built on Language Education Policy (LEP) as a conceptual framework of Baldauf and Ingram (2003) which is one of the most widely researched theoretical perspectives in language policy and planning. The findings confirmed linguistic hegemony and dominance in Bangladesh by constitution and law. The most important contribution of the article was the sociolinguistic overview of the significant language laws of Bangladesh chronologically. It provided recommendations on the development of democratic language policy in Bangladesh.Keywords: Language in the Mughal period; Language in the British period; Language in the Pakistan period; Language in the Bangladesh period; Language rights for indigenous people; Language debate; Linguistic rights.